The Search for Co-Integration Between Money, Prices and Income: Low Frequency Evidence From the Turkish Economy - (:unkn) unknown (SAVEZ EKONOMISTA VOJVODINE, 2009)
In this paper, we aim to test the empirical validity of the QTM relationship for the Turkish economy. Using some contemporaneous time series estimation techniques, our estimation results reveal that stationarity characteristics of the velocities of currency in circulation and the broad money aggregate in the economy cannot be rejected through a quantity theoretical co-integrating long-term variable space. We find that there exists an about one-to-one proportionality between money and prices and money and real income, and that exogeneity of money cannot be rejected for the currency in circulation in the economy. But, the exception here comes from the broad monetary aggregate used in the QTM equation such that money seems to be endogenous as for the long-term variable space.
Keywords: Money; Prices; Income; Quantity Theory of Money; Co-integration; Long-span Data; Turkish Economy; LONG-RUN NEUTRALITY; QUANTITY THEORY; UNIT-ROOT; GREAT CRASH; DEMAND; SHOCK